Pengembangan e-modul interaktif berbasis canva untuk meningkatkan kemampuan pemecahan masalah matematis pada materi barisan dan deret aritmatika - Adiastuty, Nuranita; Nurhayati, Nunu; Mahardhika, Tiara Dwi (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematical problem-solving skills are very important for students to master. However, students' problem-solving skills are still relatively low, one of which is in the material of arithmetic sequences and series. So it is necessary to develop teaching materials in the form of e-modules based on Canva. This study aims to develop an interactive e-module based on the Canva application as a mathematics learning medium for the topic of arithmetic sequences and series, with the goal of improving students' mathematical problem-solving skills. The research employs the Research and Development (RD) method using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research subjects were 11th-grade students at SMAN 2 Kuningan. Validation was carried out by two subject matter experts and two media experts, while practicality was assessed through questionnaires completed by students and teachers. The validation results show that the interactive e-module has a very high level of validity, with a percentage of 94.67% from the subject matter experts and 91.54% from the media experts. The practicality of the e-module is also considered very practical, with a percentage of 86% from students and 90% from the teacher. The effectiveness of the e-module was evaluated based on the improvement of learning outcomes through the N-Gain test, comparing pre-test and post-test scores. The N-Gain score of 0.61 (moderate category) indicates that the use of the Canva-based interactive e-module provides a significant and effective improvement in students’ mathematical problem-solving abilities in the topic of arithmetic sequences and series. The results of the study show that the Canva-based interactive e-module is valid, practical, and effective in enhancing students' mathematical problem-solving skills.